Activation of c-Src/HER1/STAT5b and HER1/ERK1/2 Signaling Pathways and Cell Migration by Hexachlorobenzene in MDA-MB-231 Human Breast Cancer Cell Line - Pontillo, Carolina Andrea (2011)
Hexachlorobenzene (HCB) is a widespread environmental pollutant. It is a dioxin-like compound and a weak ligand of the aryl hydrocarbon receptor (AhR) protein. HCB is a tumor cocarcinogen in rat mammary gland and an inducer of cell proliferation and c-Src kinase activity in MCF-7 breast cancer cells. This study was carried out to investigate HCB action on c-Src and the human epidermal growth factor receptor (HER1) activities and their downstream signaling pathways, Akt, extracellular-signal-regulated kinase (ERK1/2), and signal transducers and activators of transcription (STAT) 5b, as well as on cell migration in a human breast cancer cell line, MDA-MB-231. We also investigated whether the AhR is involved in HCB-induced effects. We have demonstrated that HCB (0.05μM) produces an early increase of Y416-c-Src, Y845-HER1, Y699-STAT5b, and ERK1/2 phosphorylation. Moreover, our results have shown that the pesticide (15 min) activates these pathways in a dose-dependent manner (0.005, 0.05, 0.5, and 5μM). In contrast, HCB does not alter T308-Akt activation. Pretreatment with a specific inhibitor for c-Src (4-amino-5-(4-chlorophenyl)-7-(t-butyl) pyrazolo[3,4-d]pyrimidine [PP2]) prevents Y845-HER1 and Y699-STAT5b phosphorylation. AG1478, a specific HER1 inhibitor, abrogates HCB-induced STAT5b and ERK1/2 activation, whereas 4,7-orthophenanthroline and α-naphthoflavone, two AhR antagonists, prevent HCB-induced STAT5b and ERK1/2 phosphorylation. HCB enhances cell migration evaluated by scratch motility and transwell assays. Pretreatment with PP2, AG1478, and 4,7-orthophenanthroline suppresses HCB-induced cell migration. These results demonstrate that HCB stimulates c-Src/HER1/STAT5b and HER1/ERK1/2 signaling pathways in MDA-MB-231. c-Src, HER1, and AhR are involved in HCB-induced increase in cell migration. The present study makes a significant contribution to the molecular mechanism of action of HCB in mammary carcinogenesis.